1998
DOI: 10.1182/blood.v91.2.508
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Lipoproteins Support Assembly of the Prothrombinase Complex and Thrombin Generation: Modulation by Oxidation and Vitamin E

Abstract: The importance of lipoproteins in the etiology of atherosclerosis is well established. Evidence is now accumulating to implicate thrombin in the pathogenesis of atherosclerosis. We have investigated whether atherogenic lipoproteins can support thrombin generation. In the absence of platelets or endothelial cells, both very low-density lipoprotein (VLDL) and oxidized low-density lipoprotein (LDL) support assembly of the prothrombinase complex and generation of thrombin. Thrombin generation (per μg of apolipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 47 publications
8
57
1
Order By: Relevance
“…To our knowledge, this is the first study that demonstrates an independent association between apo C-III and thrombin generation. Remarkably, our results are consistent with the previous demonstration that thrombin generation supported by VLDL, rich in apo C-III, was about twelvefold greater than that supported by LDL and twentyfold greater than that supported by HDL [33]. Moreover, apo C-III has been demonstrated to stimulate monocyte activation [9] by means of Toll-Like Receptor 2 signalling [34] and these cells are known to be involved in tissue factor-dependent thrombin generation [35].…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study that demonstrates an independent association between apo C-III and thrombin generation. Remarkably, our results are consistent with the previous demonstration that thrombin generation supported by VLDL, rich in apo C-III, was about twelvefold greater than that supported by LDL and twentyfold greater than that supported by HDL [33]. Moreover, apo C-III has been demonstrated to stimulate monocyte activation [9] by means of Toll-Like Receptor 2 signalling [34] and these cells are known to be involved in tissue factor-dependent thrombin generation [35].…”
Section: Discussionsupporting
confidence: 92%
“…It is also known that oxidised lipoproteins support the assembly of the Va/Xa (prothrombinase) complex (Rota et al 1998) and as such increase thrombin generation, as indeed our findings corroborate. Furthermore, studies in patients with antiphospholipid syndrome, which promotes a hypercoagulable state, have demonstrated that coagulation is activated by oxidative stress via overexpression of monocyte tissue factor (Ferro et al 2003).…”
Section: Exercisesupporting
confidence: 88%
“…Previously, authors have suggested that the hypoxia-induced increase in thrombin generation was associated with oxidised low density lipoprotein (LDL-OX)-mediated increased assembly of the prothrombinase complex (Rota et al, 1998) and oxidative stress increased the bioactivity of factor VIII by an as of yet unknown mechanism (Koprivica et al 2011). The existing literature regarding the thrombogenicity of hypoxia remains conflicting and our findings collectively support those that state that hypoxia alone fails to alter blood coagulation (Andrew et al 1987;Crosby et al 2003;Hodkinson et al 2003;Fall et al 2011Fall et al , 2015.…”
Section: Hypoxiasupporting
confidence: 85%
“…However, it has been shown that OxLDL delays plasmatic coagulation in vitro [24], mediated through inhibition of FVIII, FIX and FXI activity [25]. Another group, however, described increased prothrombinase activity and thrombin generation caused by OxLDL [26]. Yet another group reported that OxPLs led to increased prothrombinase activity [27].…”
Section: Oxidized Lipoproteins and Plasmatic Coagulationmentioning
confidence: 99%